Abyssomicins from the South China Sea Deep‐Sea Sediment Verrucosispora sp.: Natural Thioether Michael Addition Adducts as Antitubercular Prodrugs1. Issue 4 (6th December 2012) - Wang, Qian; Song, Fuhang; Xiao, Xue; Huang, Pei; Li, Li; Monte, Aaron; Abdel‐Mageed, Wael M.; Wang, Jian; Guo, Hui; He, Wenni; Xie, Feng; Dai, Huanqin; et al.
<x xml:space="preserve">Abstract</x> From the deep: The title actinomycete yielded three new abyssomicins J–L. The dimeric thioether J (see scheme) represents a unique example of a masked Michael acceptor with anti‐TB properties. Mechanistic insights into the biosynthesis, biomimetic synthesis, stability, and biological mechanism of action of abyssomicins aid our understanding of, and prospects for the development of Michael‐acceptor‐based drugs.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>